Hip septic arthritis and iliopsoas abscess in pertrocanteric fracture: a case report - Crescibene, Antonio; Cosentino, Orlando; Martinez Aparicio, Lazaro; Gentile, Gaetano; Ciparrone, Gualterio (Revista Cubana de Ortopedia y Traumatología, 2025)
Introduction: The number of osteoporosis- related fractures would grow to about 6 million and cost 25.4 billion annually by the year 2050. Hip fracture is one of the main consequences of osteoporosis, with devastating results for the affected patients, including markedly increased subsequent risk of fracture. Septic arthritis of the hip after femoral fracture is a rare complication. There were reports of a few cases of septic arthritis in patients following femoral neck fracture with severe medical comorbidities. Iliopsoas abscess is a rare condition with a varied symptomology and etiology. Objective: We propose to present a rare case with hip fracture. Case presentation: A 62-years -old was referred from another hospital with chronic post-traumatic subdural hematoma. After a few days he developed right hip pain; a plain radiograph showed intertrochanteric fracture of the right femur. At the hospital admission the patient was afebrile and the right hip physical examination showed no signs of inflammation or skin lesion. Microbiological examination of the pus taken from the operation site showed a positivity to Staphylococcus aureus. Post-operatively, the patient received vancomycin 1 gr twice a day intravenously and piperacillin and tazobactam 4,5 gr every 8 hours as empirical treatment for four days, later switched to daptomycin 6 mg/kg per day intravenously and continuing vancomycin according to the antibiogram results. Conclusion. Patient refused further surgical treatments.